Effect of zinc supplementation on growth, reproductive performance, immune and endocrine response in grower pigs - BORAH, S; SARMAH, B C; CHAKRAVARTY, P; NASKAR, S; DUTTA, D J; KALITA, D (The Indian Journal of Animal Sciences, 2014)
The effect of dietary supplementation of zinc (Zn) on growth and reproduction performances, thyroid hormones and globulin level was investigated in the present study. Gilts (24; average body weight 20.65±1.72 kg) were randomly assigned into 3 groups (8 animals / group) receiving a basal diet and were supplemented for 120 days with (i) 100 mg/ kg of Zn (CON); (ii) 100 mg/kg of Zn along with calcium carbonate (1.5% of dry matter of diet, to induce Zn deficiency) (DEF), or (iii) 500 mg/kg of Zn (FOR). Serum Zn level increased in FOR-fed animals, and decreased in DEF-fed compared to CON-fed. Further, DEF-fed animals developed clinical symptoms of parakeratosis. Serum Cu level was not found affected. FOR-feeding promoted tri-iodothyronine (T3) and thyroxine (T4) levels compared to CON-feeding. It also led to higher serum gamma globulin level. A reverse trend to FOR-feeding was observed in DEF-fed animals with respect to T3, T4 and γ globulin level. Better feed conversion efficiency (FCE) and higher average daily gain (ADG) was also observed with FOR-feeding. Early puberty was attained in FOR-fed animals as compared to DEF- and CON-fed. The present study suggested that dietary supplementation of Zn at 500 mg/kg level in grower pigs might help in attaining early puberty, better growth performances, improved thyroid functions and better general health.